A new Cephennodes Reitter (Coleoptera: Staphylinidae: Scydmaeninae) of C. lustricollis group from East China - Feng, Ting; Yin, Zi-Wei (Zootaxa, 2023)
The C. lustricollis group of the scydmaenine genus Cephennodes Reitter was previously represented by three species distributed in northern Vietnam and China (Hong Kong and Guizhou). Here we describe a fourth member, Cephennodes gusu sp. nov., collected from Qionglong Mountain, Suzhou, eastern China. The new species is characterized by its moderately large body size, the punctation of the head, pronotum and elytra, and the structure of the aedeagus. It is also the first record of the subfamily Scydmaeninae in Jiangsu Province.